Exploring the potential mechanisms of Rehmannia glutinosa in treating sepsis based on network pharmacology - Hao Wang; Yongchu Laram; Li Hu; Yingchun Hu; Muhu Chen (BMC Infectious Diseases, 2024)
Abstract The present study utilized network pharmacology to identify therapeutic targets and mechanisms of Rehmannia glutinosa in sepsis treatment. RNA-sequencing was conducted on peripheral blood samples collected from 23 sepsis patients and 10 healthy individuals. Subsequently, the RNA sequence data were analyzed for differential expression. Identification of active components and their putative targets was achieved through the HERB and SwissTarget Prediction databases, respectively. Functional enrichment analysis was performed using GO and KEGG pathways. Additionally, protein-protein interaction networks were constructed and survival analysis of key targets was conducted. Single-cell RNA sequencing provided cellular localization data, while molecular docking explored interactions with central targets. Results indicated significant involvement of identified targets in inflammation and Th17 cell differentiation. Survival analysis linked several targets with mortality rates, while molecular docking highlighted potential interactions between active components and specific targets, such as rehmaionoside a with ADAM17 and rehmapicrogenin with CD81. Molecular dynamics simulations confirmed the stability of these interactions, suggesting Rehmannia glutinosa’s role in modulating immune functions in sepsis.